Role of Jalaukavacharana in Management of Vicharchika w.s.r. to Eczema (AYUSHDHARA, 2025)
Kustha Roga is one among the skin disorder mentioned in science of Ayurveda. Kustha are  broadly classified into the Mahakushta and Khsudrakustha . Mahakustha is of seven type and Kshudrakustha is eleven types. Vicharchika is one among the Kshudrakustha and a type of Rakta Pradoshaja Vikara, where all three Dosha involved and Kapha is the most predominant among the three. Modern research states that eczema is the clinical manifestation of Vicharchika. Eczema is one type of dermatitis that occurs when the dermis becomes inflamed. Another name for it is atopic dermatitis, and symptoms include dry, itchy skin with ill-defined erythema and scaling. There are not enough treatment options offered by contemporary mainstream medicine. In this case study, a 66-year-old man sought consultations at the Kriya Sharir, National Institute of Ayurveda in Jaipur's OPD Department. Complained of blackish lesions over bilateral sides of left ankle associated with redness, liquid discharge and intense itching since seventeen years. The patient received allopathic treatment and consultations from allopathic hospitals, but contemporary medicine did not provide any alleviation for the patient. The patient was treated with internal medication along with five sessions of Raktamokshana using Jalaukavacharana (leech therapy). The patient had remarkable progress and the lesions were relieved.